1999
DOI: 10.1136/bjo.83.3.327
|View full text |Cite
|
Sign up to set email alerts
|

A new surgical technique for deep stromal, anterior lamellar keratoplasty

Abstract: Aims-To describe a new surgical technique for deep stromal anterior lamellar keratoplasty. Methods-In eye bank eyes and sighted human eyes, aqueous was exchanged by air, to visualise the posterior corneal surface−that is, the "air to endothelium" interface. Through a 5.0 mm scleral incision, a deep stromal pocket was created across the cornea, using the air to endothelium interface as a reference plane for dissection depth. The pocket was filled with viscoelastic, and an anterior corneal lamella was excised. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
212
2
13

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(230 citation statements)
references
References 19 publications
3
212
2
13
Order By: Relevance
“…These include layer-by-layer surgical dissection assisted by the expansion of stromal lamellae with air or balanced salt solution, blunt surgical dissection, or direct separation of Descemet's membrane from the overlying stroma with the injection of air or viscoelastic. [4][5][6][7][8][9] Initial techniques had high endothelial perforation rates (9-25% reported); however, the use of anterior chamber air to allow visualisation of the endothelium has reduced this. [5][6][7] Keratoconus is the commonest condition requiring corneal graft surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include layer-by-layer surgical dissection assisted by the expansion of stromal lamellae with air or balanced salt solution, blunt surgical dissection, or direct separation of Descemet's membrane from the overlying stroma with the injection of air or viscoelastic. [4][5][6][7][8][9] Initial techniques had high endothelial perforation rates (9-25% reported); however, the use of anterior chamber air to allow visualisation of the endothelium has reduced this. [5][6][7] Keratoconus is the commonest condition requiring corneal graft surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Initial techniques had high endothelial perforation rates (9-25% reported); however, the use of anterior chamber air to allow visualisation of the endothelium has reduced this. [5][6][7] Keratoconus is the commonest condition requiring corneal graft surgery. These patients are usually young and free from ocular comorbidity, thus making them a good group in which to study graft surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Manche et al 7 reported a technique for performing deep lamellar dissection of the cornea using viscoelastic material. Melles et al 8 described the 'air to endothelium light reflex' as a guide for the plane of dissection after filling the anterior chamber with air. In 2000, Melles et al 9 presented the viscodissection technique.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Many techniques have been introduced for accessing bare Descemet membrane (DM) as an ideal graft interface for achieving visual results comparable with penetrating keratoplasty. [3][4][5][6][7][8] However, the DM is not always bared successfully and its rupture sometimes mandates conversion to penetrating keratoplasty. One frequently used technique for exposing the DM is the big-bubble technique, which uses intrastromal air injection to create an air bubble between the DM and stroma.…”
Section: Introductionmentioning
confidence: 99%
“…Use of the big-bubble technique during DALK allows deeper dissection of the anterior corneal stroma and is known to provide enhanced visual outcomes (9,11) . However, this lamellar technique involves a long learning curve, which can pose a challenge for many corneal surgeons (10) . Several studies have shown that visual acuity (VA) in patients with keratoconus after DALK with the big-bubble technique are similar to that of those who underwent PK (12)(13)(14)(15)(16)(17)(18) , yet there is little published data with respect to preparation of the donor corneal button.…”
Section: Introductionmentioning
confidence: 99%